(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
In Argentina, after more than 30 years of legislative silence, human assisted reproduction techniques have finally found a legal framework in Argentina. The recent legislative progress in this field represents a significant outcome for individuals who have access to these procedures. The aim of this paper is to highlight the most important legal changes that have been introduced, their reasons and their constitu-tional basis. It also points out the tensions that led to the acknowledgement of assisted reproduction techniques as a fundamental means for the pluralistic evolution of family law.